Neglected arboviruses in South America: clinical manifestations and diagnostic challenges - Milagros Saavedra-Samillán; Sharon Díaz Velásquez; Marcos A Castillo Zuta; Julio Sandoval-Bances; Rafael Tapia-Limonchi; Stella M Chenet (Transactions of The Royal Society of Tropical Medicine and Hygiene, 2026)
Abstract In South America, the arboviruses that are most noted are those that lead to dengue, Zika, and chikungunya. Nevertheless, there are additional arboviruses that trigger outbreaks, yet do not receive adequate attention, including Oropouche virus (OROV), Mayaro virus (MAYV), Saint Louis Encephalitis virus, Madariaga virus (MADV), and Rocío virus (ROCV). A rapid review was conducted using the databases PubMed, LILACS, Scopus, and Google Scholar. This analysis focused on studies that outline the clinical signs and diagnostic methods of neglected arboviruses impacting human populations in South America. A total of 38 studies met the inclusion criteria. Most reports focused on OROV and MAYV, whereas only a few studies described MADV and ROCV. Brazil accounted for the largest proportion of studies, followed by Peru. Across the reviewed literature, these arboviruses were associated with a broad clinical spectrum, ranging from non-specific febrile illness to severe neurological disease and congenital complications. Diagnostic approaches included serological assays, viral isolation or neutralization tests, and molecular methods such as RT-PCR. The increasing spread of these under-reported arboviruses in South America requires strengthening monitoring systems, optimizing access to specific diagnostics, and training healthcare personnel to identify these infections early and manage them appropriately.